Seattle Children's Theatre. Volume two, six plays for young audiences - Frockt, Deborah Lynn. (Hanover, NH : Smith and Kraus, 2000)
A collection of plays dealing with family, friendship, freedom, and courage.
Includes bibliographical references.
Books for the Teen Age (NYPL).
Young Adult
Keywords: American drama -- 20th century; Children's plays, American -- Washington (State) -- Seattle; Plays -- Collections; American drama; Children's plays; Drama -- Collections